Gerakan Lansia Sehat Sebagai Upaya Peningkatan Kesehatan Lansia Hipertensi Di Desa Kedungjati, Sempor - Ernawati, Ernawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
he highest prevalence of non-communicable diseases in the elderly is hypertension. Riskesdas 2018 states that the incidence of hypertension in the elderly in Central Java based on routine blood pressure measurements is 37.57%. Public understanding of hypertension, prevention and management of hypertension, especially in the elderly is still limited. Participants in this activity amounted to 15 elderly and 2 health cadres. Education is carried out by providing material about hypertension, elderly health, and demonstrations of hypertension exercise. Hypertension exercise demonstration through video and demonstrated by the facilitator. Evaluation of education about hypertension and the health of the elderly was carried out through pre-test and post-test assessments with the result that there was an increase in knowledge of 25%. The education and demonstrations provided are proven to increase knowledge of hypertension and the ability of the elderly in hypertension exercise. It is hoped that the elderly will be able to apply a healthy lifestyle by applying hypertension exercise as an intervention to physical exercise to improve the quality of life of the elderly.